2022
DOI: 10.3389/fpls.2021.797141
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Approach for Precise Genotyping and Transcriptomics of Salt Tolerant Introgression Rice Lines

Abstract: Rice is the most salt sensitive cereal crop and its cultivation is particularly threatened by salt stress, which is currently worsened due to climate change. This study reports the development of salt tolerant introgression lines (ILs) derived from crosses between the salt tolerant indica rice variety FL478, which harbors the Saltol quantitative trait loci (QTL), and the salt-sensitive japonica elite cultivar OLESA. Genotyping-by-sequencing (GBS) and Kompetitive allele specific PCR (KASPar) genotyping, in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Tulay et al (2015) also found that salt stress increases the activity of chlorophyllase in Spergularia marina (Caryophyllaceae), decreases the content of Mg 2+ ions, accelerates the degradation of chlorophyll, inhibits the function of pigment protein complex, and the leaves become yellow or even fall off. Herein, MYB37 overexpression delayed chlorophyll degradation under salt stress and alleviated chlorophyll reduction effect, especially Chl a , similar to the results of Bundó et al (2022) . MYB37 overexpression can exhume or compartmentalize Na + in the cytoplasm into vacuoles, regulate the concentration of Na + in cells and maintain intracellular ion homeostasis by increasing the expression of Na + /H + antiporter NHX1 in the vacuolar membrane, thus delaying chlorophyll degradation and enhancing salt tolerance ( Zhao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 80%
“…Tulay et al (2015) also found that salt stress increases the activity of chlorophyllase in Spergularia marina (Caryophyllaceae), decreases the content of Mg 2+ ions, accelerates the degradation of chlorophyll, inhibits the function of pigment protein complex, and the leaves become yellow or even fall off. Herein, MYB37 overexpression delayed chlorophyll degradation under salt stress and alleviated chlorophyll reduction effect, especially Chl a , similar to the results of Bundó et al (2022) . MYB37 overexpression can exhume or compartmentalize Na + in the cytoplasm into vacuoles, regulate the concentration of Na + in cells and maintain intracellular ion homeostasis by increasing the expression of Na + /H + antiporter NHX1 in the vacuolar membrane, thus delaying chlorophyll degradation and enhancing salt tolerance ( Zhao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 80%
“…In recent years, dozens of powerful tools for quantitative trait loci (QTL) mapping have been developed based on deep sequencings, such as restriction-site associated DNA sequencing (RAD-seq), genotyping-by-sequencing (GBS), bulked segregant analysis sequencing (BSA-seq), and specific locus amplified fragment sequencing (SLAF-seq) ( Bundo et al, 2022 ). These mapping approaches used the genetic map or limited number of SNPs to seek the candidate genomic regions and genes for the traits.…”
Section: Integration Of Genomics and Phenomicsmentioning
confidence: 99%
“…RNA seq data for drought and salt stresses were assessed from online data bases which are publically available with Bio-projects GSE145869 and GSE167342 ( Tarun et al, 2020 ; Bundó et al, 2022 ). In these studies, Nil-95 and Swarna genotypes were used as drought tolerant and sensitive, while IL22 and PL12 were used as a salt tolerant and sensitive rice genotype, respectively.…”
Section: Methodsmentioning
confidence: 99%